Successful treatment of healthcare-associated Mycobacterium chimaera prosthetic infective endocarditis: the first Spanish case report. Issue 4 (6th December 2018) - Zegri-Reiriz, Isabel; Cobo-Marcos, Marta; Rodriguez-Alfonso, Begoña; Millán, Rosario; Dominguez, Fernando; Forteza, Alberto; Garcia-Pavia, Pablo; Ramos-Martinez, Antonio
Abstract: Background: Since 2011, several cases of health care-related disseminated Mycobacterium chimaera infection outbreaks have been reported subsequent to cardiac surgery. Diagnosis is difficult and the prognosis is extremely poor despite long-term antibiotic treatment and surgery. Case summary: We report a Spanish case of M. chimaera infective endocarditis (IE) with disseminated infection. The patient was treated with long-term antibiotic therapy, valve replacement, and the novel use of interferon-gamma as adjuvant therapy. In addition, [ 18 F]-fluorodeoxyglucose (FDG) positron emission tomography (PET) was used in combination with computed tomography (CT) to facilitate the diagnosis as well as to determine the duration of antibiotics and success of treatment. Discussion: Diagnosing M. chimaera IE is difficult and requires a high index of clinical suspicion. Controlling the infection is even more difficult. Interferon-g used adjuvant to surgery and antibiotic therapy could be useful in achieving this goal. Given that the appropriate duration of antibiotics is unknown, FDG PET/CT could also be a valuable tool for determining when antibiotic therapy can be withdrawn.